THE EFFECTS OF DIFFERENT TYPES OF COHESIVE DEVICES ON READING COMPREHENSION OF KOREAN LEARNERS - Bae, Miyeon (PEOPLE: International Journal of Social Sciences, 2019)
This study explores how different types of cohesive devices impact the reading comprehension for Korean as a second language learner. According to the findings, in the case of substitution, learners did not recognize the substitute expression well when they read the text. But they felt that it was more difficult to understand the text when multiple substitutions appeared within a text. In the case of conjunction, conjunctions helped learners understand the text. And in the case of ellipsis, learners who did not recognize the ellipsis read the text naturally, but the ones who did recognize it as an ellipsis responded that the meaning of the sentence was confusing and more difficult to comprehend. Finally, in the case of lexical device, repetition of the same word was helpful, but the repetition of synonym or hyponym did not help comprehend the text, because it required them to think about the relationship between the word and the synonym once more. It is hoped that the findings in this study will be of guidance to educators on how to teach cohesive devices so that the Korean language learners can effectively read and comprehend the meaning of Korean text.